DESCRIPTION OF HAPPINESS ON THE BETAWI PEOPLE IN PERKAMPUNGAN BUDAYA BETAWI SETU BABAKAN - Patnani, Miwa (Universitas Ahmad Dahlan, 2013)
AbstractHappiness is an important thing in human life, so itâs not surprisingly that people tend to do anything they could to be happy in their life. So do the Betawi people which is known as the indigenous people in Jakarta. Betawi people now facing the unpleasant reality in spite of their inability to compete with the migrants community who come and dominate the economy growth in Jakarta. This inability to compete, forces the Betawi people to move from downtown to the suburbs of Jakarta. Another impact of this inability to compete is the low level of welfare among the Betawi people, which is in turn, affects their feeling of happy. This study aimed to describe the happiness among Betawi People who lived in Perkampungan Budaya Betawi Setu Babakan, South Jakarta. Happiness questionaire was used to collect the data from 55 Betawi People. This questionaire consist of some open question and some question with alternative choices. Open questions describe the definition and sources of happiness, while question with alternative choices describe the level of happiness. The result showed that the subject of this study is quitely happy. The definition of happiness answered by the subject was categorized then, and finally revealed 7 themes: relationship within the family member, something correlated with material, having a peacefull life, something really important, achieving for what they want, physical health and to share with other people. Meanwhile, categorization on the sources of happiness found 8 sources: relationship within the family, materials, giving happiness to their beloved ones, relationship with spouses, physical health, having children, success and developing Betawi culture.Keywords: happiness, level, meaning, sources, Betawi